Progress in Engineering Technology Automotive, Energy Generation, Quality Control and Efficiency - Abu Bakar, Muhamad Husaini; Mohamad Sidik, Mohamad Sabri; Öchsner, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents recent developments in the areas of engineering and technology, focusing on experimental, numerical, and theoretical approaches. In the first part, the emphasis is on the emerging area of electromobility and its sub-disciplines, e.g. battery development, improved efficiency due to new designs and materials, and intelligent control approaches. In turn, the book's second part addresses the broader topic of energy conversion and generation based on classical (petrol engines) and more modern approaches (e.g. turbines). The third and last part addresses quality control and boosting engineering efficiency in a broader sense. Topics covered include e.g. modern contactless screening methods and related image processing.
1. Study the Effect of Acetone as an Inhibitor for the Performance of Aluminium-Air Batteries -- 2. Performance Characteristics of Palm Oil Diesel Blends in a Diesel Engine -- 3. Optimization of Palm Oil Diesel Blends Engine Performance based on Injection Pressures and Timing -- 4. The Potential of Improving the Mg-alloy Surface Quality Using Powder Mixed EDM.
Keywords: Materials; Catalysis; Force and energy; Energy policy; Energy and state; Materials for Energy and Catalysis; Materials Engineering; Energy Policy, Economics and Management